2008
DOI: 10.1677/erc-08-0153
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box-O transcription factor: critical conductors of cancer's fate

Abstract: Cells have evolved elaborated mechanisms to coordinate the cellular answer of either survival or apoptosis. Recent concepts of human carcinogenesis have suggested disturbances in these cellular relays as a potential link to cellular dedifferentiation and uncontrolled proliferation. Forkhead box-O transcription factors (FOXOs) play an important role in tumour suppression by regulating the expression of genes involved in stress resistance, DNA damage repair, cell cycle arrest and apoptosis. The specific regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 99 publications
2
39
0
Order By: Relevance
“…FoxO transcription factors regulate diverse cell functions (Accili and Arden, 2004) through regulation of genes involved in cell proliferation and apoptosis (Weidinger et al, 2008). Specifically, FoxO3a has been reported to activate genes that induce cell cycle arrest, such as p27 (Dijkers et al, 2000), p21 (Seoane et al, 2004), p15 and p19 (Katayama et al, 2008), and to suppress the expression of cyclin D2 (Fernandez de Mattos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…FoxO transcription factors regulate diverse cell functions (Accili and Arden, 2004) through regulation of genes involved in cell proliferation and apoptosis (Weidinger et al, 2008). Specifically, FoxO3a has been reported to activate genes that induce cell cycle arrest, such as p27 (Dijkers et al, 2000), p21 (Seoane et al, 2004), p15 and p19 (Katayama et al, 2008), and to suppress the expression of cyclin D2 (Fernandez de Mattos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…28 FOXO3a expression in ovarian cancer is largely unknown. Fei et al 29 studied a total of 63 ovarian cancer cases and found that low FOXO3a expression was significantly associated with worse clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FOXOs induce expression the sterol carrier proteins SCPx/SCP2, which stimulate peroxisomal metabolism of branchedchain FAs, protect FAs against peroxidation, and function to mitigate the toxicity of oxidized lipids such as cholesterol hydroperoxide (Weinhouse 1976;Dansen et al 2004;Samuel et al 2006;Zhang et al 2006;Weidinger et al 2008;Kriska et al 2010).…”
Section: Metabolic Alterations Supporting Balanced Redox Status Reactmentioning
confidence: 99%